2007
DOI: 10.1002/cm.20245
|View full text |Cite
|
Sign up to set email alerts
|

Tropomyosin 4 defines novel filaments in skeletal muscle associated with muscle remodelling/regeneration in normal and diseased muscle

Abstract: The organisation of structural proteins in muscle into highly ordered sarcomeres occurs during development, regeneration and focal repair of skeletal muscle fibers. The involvement of cytoskeletal proteins in this process has been documented, with nonmuscle gamma-actin found to play a role in sarcomere assembly during muscle differentiation and also shown to be up-regulated in dystrophic muscles which undergo regeneration and repair [Lloyd et al.,2004; Hanft et al.,2006]. Here, we show that a cytoskeletal trop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 34 publications
3
28
0
Order By: Relevance
“…We demonstrated previously that a cytoskeletal Tm from the ␥-TM gene, Tm5NM1, localizes to the sarcolemma and to a region adjacent to the Z-line in skeletal muscle fibers . In addition, we have shown that Tm4, the single product of the ␦-TM gene, is also found in this region and in longitudinal filaments in regenerating or repairing muscle (Vlahovich et al, 2008). Both Tm5NM1 and Tm4 colocalize with a ␥-actin cytoskeleton at these sites, suggesting a role for these filament systems in stabilization of the muscle fibers and linking myofibrillar networks to the membrane systems.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…We demonstrated previously that a cytoskeletal Tm from the ␥-TM gene, Tm5NM1, localizes to the sarcolemma and to a region adjacent to the Z-line in skeletal muscle fibers . In addition, we have shown that Tm4, the single product of the ␦-TM gene, is also found in this region and in longitudinal filaments in regenerating or repairing muscle (Vlahovich et al, 2008). Both Tm5NM1 and Tm4 colocalize with a ␥-actin cytoskeleton at these sites, suggesting a role for these filament systems in stabilization of the muscle fibers and linking myofibrillar networks to the membrane systems.…”
Section: Introductionmentioning
confidence: 84%
“…Mouse muscles were fixed in 4% paraformaldehyde (PFA) (hindlimb muscles were stretched and held during fixation) and infused with 1.8 M sucrose/20% polyvinylpyrrolidone as described by Vlahovich et al (2008). Semithin (0.5-to 0.8-m) sections were cut at Ϫ60°C using an Ultracut UCT ultramicrotome (Leica, Wetzler, Germany) equipped with an EM FCS cryochamber (Leica).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…3A, mXin␣ was coimmunoprecipitated from gastrocnemius muscle extracts using anti-tropomyosin (LC24), antifilamin, anti-vinculin, or anti-talin mAb but not anti-␤-catenin mAb or normal mouse serum control. mAb LC24 recognizes tropomyosin isoform 4 that is known to locate together with ␥-actin external to the sarcomere but adjacent to the Z-line and in the subsarcolemmal region including MTJ in skeletal muscle cells (28,58). The antibodies used in our experiments specifically precipitated their respective antigens from skeletal muscle extract except for anti-␤-catenin (Fig.…”
Section: Similar But Distinguishable Localizations For Mxin␣ and Mxinmentioning
confidence: 98%
“…Specifically, the Tm4 isoform is involved in recruitment of myosin II to stress fibers in U2OS cells (Tojkander et al, 2011). Interestingly, TPM4 might also contribute to the assembly of premyofibrils (Vlahovich et al, 2008) and to myosin-IIA-rich podosome cores of osteoclasts (McMichael et al, 2006), suggesting that the role of this TPM isoform in the formation of distinct myosin-based structures is conserved. TPMs also regulate actomyosin interactions, including the assembly of contractile ring in fission yeast Clayton et al, 2010).…”
Section: Regulation Of Stress Fiber Contractionmentioning
confidence: 99%